Arctic Crossing: A Journey Through the Northwest Passage and Inuit Culture - Waterman, Jonathan (Alfred A. Knopf, 2001)
Describes the author's journey from the Inuit communities in Alaska, across the Northwest Passage, to Nunavut in Canada, and the physical and psychological challenges he encountered along the way.
Keywords: Non-Fiction; Travelogues